Boosting the English Vocabularies of Young Learners through Tik-Tok Application in Digital Era - Daniar Sofeny; Dian Fadhilawati; Ninik Nuzulul Hidayah (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
Tik-Tok Application is one of application that are great demand by people in this digital Era, no exception for the children in Elementary school. This study examined about how the students’ vocabulary score before and after taught by using the Tik-Tok application and whether there was any significant difference of students’ score before and after taught by using Tik-tok application. The researcher used the method of pre-experimental design using one group pretest-posttest with quantitative approach. The instrument used to obtain the data was test. The hypothesis itself was tested by using T-test technique. From the data obtained, the average total score of students' vocabulary mastery before taught by using the Tik-Tok application was 55.00 and the average score of students’ vocabulary mastery after taught by using the Tik-Tok application was 86.87. Statistical calculations using T-test have shown the results of tcount (14,586) and the result of ttable for standard 0.050% is 2.03951. It is known that tcount is higher than ttable (14.586 > 2.03951). The alternative hypothesis is accepted, and the null hypothesis is rejected. Based on the result of this research, the students’ score of vocabularies were increase from 55,00 to 86,87. Then the second result is, there were significant differences scores, between before and after receiving treatment by using the Tik-Tok application. So, Tik-tok application is effective for the teacher who want to increase the students’ English vocabularies mastery.